Melacak Kebijakan Politik Terhadap Etnis Tionghoa Di Indonesia - Putri, Risky Ananda; Zaina, Murni; Rizki, Fadilah (Indonesian Democracy Research Center, 2022)
The beginning of the arrival of ethnic Chinese to Indonesia to conduct trade because Indonesia is a strategic area for trade. Then the ethnic Chinese settled in Indonesia until Indonesia became independent. With this, the government set special policies on ethnic Chinese who settled in Indonesia. This research aims to find out the political policies towards ethnic Chinese in Indonesia. This research method uses a literature study. Data collection is done by reviewing and exploring several journals, books, newspapers and documents in print and electronic form. The data analysis technique used is Content Analysis. The results of this study indicate that the policies initiated against ethnic Chinese are inseparable from the G30S/PKI event. Policies issued during the New Order era tended to discriminate against ethnic Chinese. The collapse of the new order regime began to support the struggle for ethnic Chinese equality such as establishing policies concerning the status of ethnic Chinese citizenship.